Procalcitonin in Preterm Neonates: A Different Threshold and Prolonged Interpretation - Bianco, Blandine; François-Garret, Bérengère; Butin, Marine; Dalmasso, Cyril; Casagrande, Florence; Mokhtari, Mostafa; Eleni Dit Trolli, Sergio (Frontiers in Pediatrics, 2021)
OBJECTIVES: To evaluate the positive threshold of PCT for neonates of less than 32 weeks of gestation for the diagnosis of early-onset sepsis and to determine if the level of PCT collected within 6 hours of life could be used DESIGN: Retrospective and bicentric study from May 2016 to April 2018 SETTING: Two groups were established, neonates evaluated for PCT at birth (CordPCT) and within six hours of life (delPCT). PATIENTS: 260 neonates of less than 32 weeks of gestation born in Nice and South Paris (Bicêtre) University Hospitals, had been evaluated for PCT level. MAIN OUTCOMES MEASURES: The value of the PCT positive threshold was determined for the total population and each groups thanks ROC curves . RESULTS: The threshold level of PCT for the total population was 0.98 ng/ml. The threshold value of cordPCT group was 1.00 ng/ml vs 0.98 ng/ml for delPCT group. The area under the Receiver Operating Characteristics curve for PCT sampled in delPCT group was significantly higher than in cordPCT group (0.94 compared to 0.75). CONCLUSIONS: The threshold level of PCT was higher in this cohort of neonates of less than 32 weeks of gestation compared to the value generally described for term neonates. The secondary sampling PCT level seems to be usable in screening algorithm for early-onset neonatal sepsis.